Enhancement of methane production from anaerobic digestion of grease trap waste - Rasit, Nazaitulshila (2016)
Research on waste recovery option as part of waste management strategy has become increasingly important for environmental sustainability. In anaerobic digestion, less attention has been focused on the digestion of grease trap waste (GTW) as a single substrate may be due to high lipid content contained in GTW that may cause inhibition effects resulted from long chain fatty acids (LCFA) accumulation. The inhibition behaviour of GTW as a single substrate in anaerobic digestion using continuous stir tank reactor (CSTR) with appropriate operating conditions are investigated. The aim of this study is to investigate various strategies to enhance methane production from anaerobic digestion of GTW. Thus, the objectives set up were to evaluate the influence of acclimated and non-acclimated inoculum, investigate the feasibility of glycerine supplementation, evaluate the performance of different feeding pattern strategy and model the reaction kinetics of grease trap waste anaerobic digestion. Four reactors were set-up as RAB for acclimated (LCFA) to biomass reactor, RGS for glycerine supplementation reactor, R12H for feeding every 12 hours reactor and Rcontrol for control and comparison with other reactors. The experimental works were conducted in two phases, which is the first phase is a start-up operation, where the reactors were run in batch experiments. Then, the second phase is the semi-continuous feeding operation with increasing organic loading rate (OLR) ranging from 1.3-3.6 gCOD/L.day. The performance of all reactors was evaluated based on methane composition, production rate and yield.The strategy of acclimated inoculum to LCFA (RAB) and glycerine supplementation (RGS) were demonstrated to enhance methane production performance. In RAB reactor, there is no lag phase was observed during the start-up of the process, where the other reactors using non-acclimated inoculum were observed (RAB, R12H and Rcontrol). Without lag phase, RAB reactor showed the highest methane production performance as compared to Rcontrol when methane composition recorded was 71% with 0.455 LCH4/L.day of methane production rate and 0.22 LCH4/gCODremoved of methane yield at OLR of 2.2 OD/L.day. In RGS reactor, a reduction of 5 days lag phase was observed as compared to Rcontrol which experienced 9 days lag phase with 67% methane composition, 0.376 LCH4/L.day of methane production rate and 0.19 LCH4/gCODremoved of methane yield at OLR of 2.2 gCOD/L.day. R12H (2 times feeding per day) reactor has shown less efficiency in terms of methane enhancement as compared to Rcontrol (1 time feeding per day) reactor. Increasing feeding frequency does not enhance methane production when methane composition recorded was 57% with 0.269 LCH4/L.day of methane production rate and 0.14 LCH4/gCODremoved of methane yield during OLR of 2.2 gCOD/L.day as compared to Rcontrol when methane composition recorded was 60% with 0.287 LCH4/L.day of methane production rate and 0.14 LCH4/gCODremoved of methane yield at the same OLR. The experimental results were well fitted in Monod and Contois kinetic models. High relationship between experimental and simulated results were obtained with high correlation coefficients (R2) ranging from 0.96-0.98. Overall, the efficient strategies to enhance methane productions were evaluated from RAB and RGS reactor when overall methane enhancement were 42% and 25%, respectively. Accordingly, the kinetic models used in the study can be used to foresee the performance of the reactor for anaerobic digestion system treating GTW.